Navigating Digital Frontiers: Estonia’s e-Residency through the Lens of the Eclectic Paradigm - Luhur, Ken Budi; Trihartono, Agus; Hara, Abubakar Eby (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
The Estonian e-Residency program, launched in 2014, allows non-residents to access Estonia’s advanced digital infrastructure and services. It provides a secure digital identity to individuals worldwide, enabling them to start and manage a location-independent business online within the European Union without needing to physically reside in Estonia. This study explores the opportunities and challenges of e-Residency through qualitative methods and the Eclectic Paradigm model by John Dunning. While e-Residency does not grant physical residency, citizenship, or tax residency, is especially attractive to individuals seeking to leverage Estonia’s advanced digital infrastructure and favorable business environment. Key opportunities include leveraging Estonia’s advanced digital infrastructure and accessing the European Union market, significantly enhancing business efficiency and economic participation. However, the novelty of the e-Residency concept still faces challenges from the challenge of low global adoption, which requires optimization for broader relevance and impact. Lastly, this research underscores the need for strategic improvements to maximize the program’s potential and suggests further development to achieve its global aspirations. Keywords: e-Residency, Digital Identity, Estonia, Eclectic Paradigm Program e-Residency Estonia, yang diluncurkan pada tahun 2014, memungkinkan non-residen untuk mengakses infrastruktur dan layanan digital canggih Estonia. Program ini menyediakan identitas digital yang aman bagi individu di seluruh dunia, yang memungkinkan mereka untuk memulai dan mengelola bisnis daring yang tidak bergantung pada lokasi di Uni Eropa tanpa perlu bertempat tinggal secara fisik di Estonia. Studi ini mengeksplorasi peluang dan tantangan e-Residency melalui metode kualitatif dan model Paradigma Eklektik oleh John Dunning. Penelitian ini menemukan bahwa meskipun e-Residency tidak memberikan tempat tinggal fisik, kewarganegaraan, atau pajak tempat tinggal, tetapi sangat menarik bagi individu yang ingin memanfaatkan infrastruktur digital canggih Estonia dan lingkungan bisnis yang menguntungkan. Peluang utama termasuk memanfaatkan infrastruktur digital canggih Estonia dan mengakses pasar Uni Eropa, yang secara signifikan meningkatkan efisiensi bisnis dan partisipasi ekonomi. Namun, di sisi lain, kebaruan konsep e-Residency masih mengalami tantangan berupa adopsi global yang masih rendah sehingga memerlukan pengoptimalan untuk relevansi dan dampak yang lebih luas. Terakhir, penelitian ini menggarisbawahi perlunya peningkatan strategis untuk memaksimalkan potensi program dan menyarankan pengembangan lebih lanjut untuk mencapai aspirasi globalnya. Kata-kata Kunci: e-Residency, Identitas Digital, Estonia, Paradigma Eklektik